2009
DOI: 10.1111/j.1945-1474.2009.00051.x
|View full text |Cite
|
Sign up to set email alerts
|

Facilitating Follow-Up after Emergency Care Using an Appointment Assignment System

Abstract: Many emergency department (ED) patients require urgent follow-up in primary care. The most effective way to help patients obtain their needed after-visit care is to secure the appointment on their behalf prior to their departure from the ED. This study describes the development, implementation, and outcomes of an appointment assignment system that facilitates patient follow-up at two community hospitals in an integrated healthcare system. This patient-centered system resulted in a high rate of compliance and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 20 publications
0
14
0
Order By: Relevance
“…Papers in the Follow-up compliance and its predictors theme group assessed the frequency of follow-up care among discharged ED patients, as well as the factors (some adjusted, some univariate) associated with obtaining follow-up care. For organizational purposes, we further subdivided papers into general follow-up compliance and its predictors (13 papers), 17,18,20,23,30,32,33,37,39,40,42,43,47 those specifically for patients with asthma (11 papers), 16,21,25,28,41,45,[48][49][50]52,53 studies that provided an appointment (date and time) prior to ED departure (11 papers), 22,26,27,29,31,[34][35][36]44,46,51 and studies that provided an appointment but not during the ED visit (three papers). 19,24,38 As shown in Table 4, the provision of an outpatient follow-up appointment prior to ED discharge was tested in five randomized controlled trials (RCTs).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Papers in the Follow-up compliance and its predictors theme group assessed the frequency of follow-up care among discharged ED patients, as well as the factors (some adjusted, some univariate) associated with obtaining follow-up care. For organizational purposes, we further subdivided papers into general follow-up compliance and its predictors (13 papers), 17,18,20,23,30,32,33,37,39,40,42,43,47 those specifically for patients with asthma (11 papers), 16,21,25,28,41,45,[48][49][50]52,53 studies that provided an appointment (date and time) prior to ED departure (11 papers), 22,26,27,29,31,[34][35][36]44,46,51 and studies that provided an appointment but not during the ED visit (three papers). 19,24,38 As shown in Table 4, the provision of an outpatient follow-up appointment prior to ED discharge was tested in five randomized controlled trials (RCTs).…”
Section: Resultsmentioning
confidence: 99%
“…Multiple studies have shown an association between obtaining timely follow-up care and better subsequent patient outcomes, but all of these studies limited their patient inclusion criteria to specific groups (those with heart failure, atrial fibrillation, and low-risk chest pain). [107][108][109][110][111] Patient selection criteria among all the studies included in our scoping study varied widely: some studies included all discharged patients (no risk stratification was applied), [34][35][36]42,47,57,[59][60][61]63,65,66,69,71,72,75,76,80,92,93,97 others limited the cohort to patients with certain diseases (e.g., asthma, hypertension) or acute conditions that would reasonably require follow-up care (e.g., possible ectopic pregnancy, low-risk chest pain patients), [16][17][18][19]21,[24][25][26]28,32,33,38,39,41,[43][44][45][46]…”
Section: Defining Who Needs the Appointmentsmentioning
confidence: 99%
“…The reasons listed by the treating physician for not attempting cardioversion (more than one reason could be noted) included frequent recurrences of atrial dysrhythmia (n = 14; 93.3%), relevant comorbidities or sedation risk (n = 9; 60.0%), and prior failed cardioversion attempt (n = 2; 13.3%). The majority of these patients received IV rate reduction medication in the ED (Table 3) and was discharged home (Table 4) on rate-control medications and anticoagulation with arranged timely follow-up with their primary care provider or cardiologist (14). Because this group of patients was thought to be ineligible for cardioversion, they were not advised to return to the ED within 48 h of symptom onset as in the ''short-term home observation'' group.…”
Section: Contraindicated Cardioversion: Participants Deemed Ineligiblmentioning
confidence: 97%
“…This would allow sufficient time for attempted cardioversion within the 48-h window for those who might fail to spontaneously convert. Eleven of these home observation patients were instructed to return directly to the ED, and 5 were arranged urgent follow-up in the clinic (3 in the Cardiology Clinic and 2 with their primary care provider) (14). All 16 patients returned as directed and 11 (68.8%) were found to have spontaneously converted.…”
Section: Attempted Cardioversionmentioning
confidence: 99%
“…If patients who are unlikely to comply with follow up can be identified while still in the ED, the management plans for these individuals could be tailored to their specific needs or circumstances. This might help ensure the successful completion of their therapy and prevent adverse outcomes or representation to the ED …”
Section: Introductionmentioning
confidence: 99%